1983
DOI: 10.1002/j.2050-0416.1983.tb04215.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of the Major Antigenic Beer Protein of Barley Origin

Abstract: The major antigenic beer macromolecule, Antigen 1, has been isolated from commercial lager beer by succesive use of ultrafiltration, alcohol precipitation, anion exchange, cation exchange and gel filtration chromatography. Amino acid analyses showed a composition identical with that of a major barley albumin, Protein Z, except for a 16% lower content of lysine. Like Protein Z, Antigen 1 showed a molecular weight (MW) near 40,000 in gel filtration and SDS‐gel electrophoresis. Unlike Protein Z, Antigen 1 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
6

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 11 publications
(2 reference statements)
4
49
0
6
Order By: Relevance
“…Protein Z comprises a family of serine proteinase inhibitors (Dahl et al 1996), which have been associated with specific effects on beer quality, in particular the stabilisation of beer foams (Hejgaard and Kaesgaard 1983). However, Lusk et al (1995) demonstrated that protein Z alone was not the main foam-stabilising protein in beer foam.…”
Section: Protein Zmentioning
confidence: 99%
“…Protein Z comprises a family of serine proteinase inhibitors (Dahl et al 1996), which have been associated with specific effects on beer quality, in particular the stabilisation of beer foams (Hejgaard and Kaesgaard 1983). However, Lusk et al (1995) demonstrated that protein Z alone was not the main foam-stabilising protein in beer foam.…”
Section: Protein Zmentioning
confidence: 99%
“…1A) at about 43 kDa, corresponding to the protein Z 15 , is evident in all the samples. The two Weissbiers (Franziskaner Dunkel and Franziskaner) show a distinctive protein electrophoretic pattern (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Beer contains a variable amount (20-600 mg/L) of proteins 29 , with molecular masses from about 5 kDa up to more than 100 kDa 26 , arising mainly from malted barley or from other cereals (such as wheat, maize, rice…) employed in beer production. It has previously been reported that these proteins are partially glycated through the Maillard reactions that occur during the diverse technologies for malt and wort production and processessing 15,16 . The glycation of proteins improves their capacity to form and stabilize foam 2,7 , and additionally prevents their precipitation/flocculation 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Protein Z is the most abundant malt and beer protein and has been identified as a major beer antigen 70 and the first plant member of the serpin superfamily 71 . However, investigation of its role in beer quality, as well as its modification during the brewing process, is still an active research area.…”
Section: Serpin (Protein Z)mentioning
confidence: 99%
“…Multiple spots of protein Z have been observed on malt and beer 2D gels 67,78,79,130 . Protein Z contains 20 lysines per molecule; glycation occurs during the malting and brewing process and 16% of the lysine content has been found glycated upon brewing 70 .…”
Section: Serpin (Protein Z)mentioning
confidence: 99%